DETERMINING CRITICAL SUCCESS FACTORS OF INFORMATION SECURITY KNOWLEDGE TOWARDS ORGANISATIONS' INFORMATION SECURITY EFFECTIVENESS : - Rohana Mohamad Rashid (Tesis, 2020)
This thesis is seek to investigate the critical success factors of information security knowledge (ISK) in Malaysian public sector organisation (MPSO). Through systematic literature review (SLR), this thesis proposes five critical success factors of ISK that affect the organisations' information security effectiveness. These critical success factors are knowledge, employee behavior, knowledge sharing, motivation and protection of information.